Formal modeling and analysis of timed systems : 17th international conference, FORMATS 2019, Amsterdam, the Netherlands, August 27-29, 2019 : proceedings /: 17th international conference, FORMATS 2019, Amsterdam, the Netherlands, August 27-29, 2019 : proceedings. ([2019]) - Unknown
No abstract available